Diseño experimental de un inhibidor natural a base de la planta althaea officinialis para la prevención de incrustaciones inorgánicas de carbonato de calcio en las tuberías de producción a escala de laboratorio (2021)
The formation of inorganic fouling in the oil industry, specifically in the field of production, has been one of the major problems of the hydrocarbon sector. These, due to their complexity in treatment, cause difficulties that can compromise the useful life of the well, from situations associated with damage to the formation, which negatively impacts the production and makes it essential the use of chemical additives, which mostly lead to other collateral effects such as corrosion and environmental affectation caused by the eutrophication of the water when applying chemicals that lead to the generation of these new problems. Considering the above, this work has a detailed procedure for the generation of a natural inhibitor from the plant Althaea Officinalis, based on successful results of similar products (INTAV-Aloe vera), and following primordial parameters of green chemistry. The product obtained was characterized and evaluated from the application of NACE TM 0374 in 2007, Langelier Saturation Index, and the current methodology of efficiency assessment of natural inhibitors based on existing models.